Evaluasi Unjuk Kerja Pompa Produk Avtur di Integreted Terminal PT Pertamina Patra Niaga Wayame Ambon - Marcelino Pattiasina; Erwin. B. Pattykayhattu; Roy. R. Lekatompessy (Department of Mechanical Engineering, 2023)
Performance evaluation for avtur pumps is needed as a review medium to make decisions. Avtur pumps that work continuously will cause a decrease in performance. This can be caused by several factors such as pump age and roughness that cause an increase in head loss. Reduced head loss will affect the power generated and the NPSH value of the pump. The purpose of this study is to determine the increase in Head loss of pump 4B Avtur products at the Integreted Terminal of PT. Pertamina Patra Niaga Wayame Ambon and its effect on the power generated and NPSH value of the pump. This research was conducted quantitatively with 2 variables. Variable free head loss pump 4b avtur product while variable bound pump power and NPSH pump. The data obtained are divided into two types, namely primary data and secondary data. The method used to obtain data is by observation, experimentation and liturature. The results of this study are known that the pump is centrifugal type. There was an increase in pump head loss by 0.128 m. the increase in head loss affected the increase in output power by 0.01 kW or about 100 watts per use. The available NPSH value and the required NPSH value were also affected, which was initially 5.42 > 4.36 to 5.47 > 4.37. The advice given is that the pump must still be considered and improved maintenance and inspection schedules because it is seen from the life of pumps that have worked for more than 10 years. Keyword : head loss, npsh, output power, centrifugal pump